MODERN ASPECTS OF ARCHITECTURAL PLANNING IMPROVEMENT OF UNIVERSITY CAMPUSES: Array (Municipal economy of cities. Series: «Economy science», 2018)
Progress in science and education, changing social needs and expanding the range of functions of higher education institutions, the investment attractiveness of these facilities, the introduction of domestic targeted programs for the development of campuses in urban development, the lack of a modern regulatory framework, and more requires addressing the design and development of University campuses. Modern aspects of architectural and planning design of these objects are divided into seven main blocks: urban planning, functional planning, composition, socio-economic, environmental, constructive, engineering and technical. The town-planning block considers the location of the campus in the structure of the city, its connection with the surrounding buildings, territorial reserves for development, pedestrian and transport framework and recreational resource. Functional planning block considers the relevance of the functional program and planning solutions of the campus, communication links, the main functional areas, barrier-free environment, multi-functionality objects, the relationship of space and informative environment. Composite unit explores the principles of formal and colors and techniques of the aestheticization of the environment. Socio-economic unit considers the feasibility and architectural and planning solution, economic efficiency and social significance of the University. The environmental unit considers the issues of the University’s safe impact on the environment and the environment on campus residents. The structural unit considers the safety of buildings and the effectiveness of their design solutions. The engineering and technical unit considers issues of engineering infrastructure and maintenance of the campus. As conclusions the main recommendations for design are given, including the composition structure, balance of functional zones and technical and economic indicators. Keywords: university, campus, function, improvement, planning, environment, comfort.